XSL transformations: A delivery medium for executable content over the Internet - Bayram, Zeki; Onder, Ruhsan (My University, 2007)
Extensible Stylesheet Language Transformations (XSLT) is a language processor and a code compilation and delivery medium for executable content over the Internet. The operational semantics of the minimum imperative language XIM in XSLT specifies the meaning of a program in a source language, by giving rules for the changes in source language. XSLT stylesheet implements the operational semantics of XIM and the stylesheet transforms the XIM program to be implemented. The basic structure of the code that processes the XSLT client input includes XmlDocument containing the XMI code, user input parameter, interpreter stylesheet, and modifying the document in file. The processing instruction indicating the name of the stylesheet to be applied to the XSLT document is inserted into the code to deliver it through the Internet.